Determination of Trace Element Nutrition and Risk Assessment of Heavy Metals in Se-Enriched Camellia oleifera by ICP-MS - Ma, Jinlin; Zhang, Riqing; Ye, Hang; Wang, Jing; Li, Xuguang; Wang, Qi; Miao, Chunyu; Rui, Yukui (Asian Journal of Chemistry, 2013)
Camellia oleifera and Se elements both have health care function for human body, but Se-enriched Camellia oleifera has not been studied. The changes of trace elements and heavy metals contents of Camellia oleifera seed after selenium enriching were studied. The results showed that (1) Selenium can promote the absorption of Camellia oleifera seeds to Li, P, K, Si and Mg; (2) Selenium can promote the absorption of Camellia oleifera seeds to many trace elements beneficial for human health including Ca, Fe, Cu and Mo; (3) Selenium can reduce the absorption of Camellia oleifera seeds to Hg, Pb, Ti and Ni. It is suggested that selenium can improve the nutrition of Camellia oleifera oil and reduce the risk of heavy metals.